Sustainable development through Corporative Social Responsability, Corporative Philanthropy and Creating Shared Value - Becerra-Vicario, Rafael; León-Gómez, Ana; Gutiérrez-Ruiz, Antonio Manuel; Fernández-Gámez, Manuel Ángel (Technium Social Sciences Journal, 2020)
This paper analyses the “strategic philanthropy” proposal, made by professors Porter and Kramer, according to which, a company’s social responsibility must lead to the agreement between social benefit and economic benefit. The company intentionally identifies the key areas in which the community and shareholders’ interests are related so they can take certain measures that improve each other’s conditions. With that in mind, companies should focus on those philanthropy activities that fortify their competitiveness, that is, those activities that equal a progress in the situation of the productive factors and requirements of demand. Drawing from this approach of creating social and economic value, we carried out a study of the main international corporations in which the public and the company’s interests are the same thus appearing new opportunities of creating shared value.